Pengembangan Media Wayang Kartun Untuk Meningkatkan Keterampilan Menyimak Pada Tema 2 Subtema 1 Siswa Kelas III SDN 091407 Sarimatondang - Doharma Evita Mayasari Sidabutar; Erlinda Simanungkalit; Dody F Pandimun Ambarita; Faisal Faisal; Waliyul Waliyul (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
This research aims to determine the feasibility, practicality and effectiveness of Cartoon Puppet Media to improve students' listening skills in Theme 2 Sub-theme 1 for Class III Students at SD N 091407 Sarimatondang. This research is research and development using the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. Based on the research results obtained, validation by media experts obtained 90% in the "Very Appropriate" category, validation by material experts obtained 84% in the "Very Appropriate" category, practicality test results by education practitioner experts obtained 90% in the "Very Practical" category. The results of the students' listening skills test were with an average pre-test score of 60.8 with a completion percentage of 25% in the "Not Effective" category. Meanwhile, from the post-test results, an average score increase of 90.2 was obtained with a completion percentage of 100% in the "Very Effective" category. From these results it can be concluded that Puppet Cartoon media is feasible, practical and effective to use to improve students' listening skills.